2010
DOI: 10.1017/s1751731109991273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on spermiogram of Holstein Friesian × Sahiwal crossbred bulls

Abstract: This study was conducted on 94 Frieswal (5/8 Holstein Friesian 3/8 Sahiwal) crossbred bulls of three different grades, categorized based on their semen freezability visualising Group 1 (consistently freezable semen producer bulls, N 5 11), Group 2 (inconsistent freezable, N 5 16) and Group 3 (Non freezable, N 5 67). Each group was further divided into two classes that is young (up to 30 months) and adult (31 to 70 months) bulls depending upon their age. Sperm morphology was studied by using the eosin-nigrosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 18 publications
9
32
3
1
Order By: Relevance
“…The semen production is affected by season (Singh et al 2000;Mathur et al 2002;Bhoite et al 2005) as well as period (Bhoite et al 2005). Age also affects semen production as reported by various workers (Sudheer 2000;Mandal et al 2010). The average age at first semen collection of crossbred bulls is about 29 months in Jersey ź Zebu (Suryaprakasam and Rao 1993).…”
Section: Introductionmentioning
confidence: 77%
“…The semen production is affected by season (Singh et al 2000;Mathur et al 2002;Bhoite et al 2005) as well as period (Bhoite et al 2005). Age also affects semen production as reported by various workers (Sudheer 2000;Mandal et al 2010). The average age at first semen collection of crossbred bulls is about 29 months in Jersey ź Zebu (Suryaprakasam and Rao 1993).…”
Section: Introductionmentioning
confidence: 77%
“…These differences in observations support our view that crossbreeding of B. indicus with B. taurus might result in a gene pool in the crossbred which is responsible for low testosterone concentrations. Earlier studies involving comparisons for sexual behavior and seminal attributes in Ongole (zebu) and Jersey x Ongole crossbred bulls (Rao et al 1996) as well as Sahiwal and Holstein Freisian x Sahiwal crossbred bulls (Mandal and Tyagi 2004;Mandal et al 2008) also provide evidence for poor sexual behavior and semen quality in crossbred bulls. Post et al (1987) demonstrated that plasma testosterone response to GnRH was highly variable in zebu x British crossbred bulls despite the fact that the bulls were selected for uniformity of breed, age, and size.…”
Section: Discussionmentioning
confidence: 97%
“…Many authors using different staining methods describe various morphologic abnormalities of sperm in bulls (Revay et al 2009, Freneau et al 2010, Mandal et al 2010, Enciso et al 2011, stallions (Kavak et al 2004, Morrell et al 2008, Einarsson et al 2009, Brito et al 2011, Love 2011, rams (Lambrechts et al 2000, Janett et al 2001, Sweeney et al 2007, Lopez Armengol et al 2012) and dogs (Kawakami et al 2005, Nxñ ez-Martinez et al 2005, Peñ a et al 2007, Lange-Consiglio et al 2010). But we did not find concrete references what is the morphologically normal sperm cell in domestic animals.…”
Section: Introductionmentioning
confidence: 99%